Analisis Kebutuhan Air Irigasi dan Keuntungan Produksi Tanaman Dengan Alternatif Waktu Tanam di Daerah Irigasi Barumun Kabupaten Padang Lawas Sumatra Utara - S, Dedy Indriatmo; Andajani, Sih (Sekolah Tinggi Teknologi Pekanbaru, 2023)
Rice fields around the Barumun River, Padang Lawas Regency, North Sumatra Province are generally rainfed rice fields. To increase the production of agricultural products, rainfed rice fields need to be upgraded into technical irrigation areas. Farmers in this area plant corn crops during the dry season, so the cropping pattern that can be applied is rice-rice corn. The available area around the Barumun River that can be used as rice fields is an area of ??3,128 ha with the Barumun River as the source of irrigation water. Of the 24 alternatives for starting rice planting, the potential area of ??rice and corn can be calculated, and it can be determined whether the entire 3,128 ha area can be irrigated by the Barumun River by gravity throughout the year. The method used in this calculation is the water balance method. From the results of the calculation of 24 alternative planting times, the alternative that produces the maximum land area and profit is alternative 21. The value of the planned irrigation water requirement which will be needed later to calculate the capacity of irrigation canals and buildings is 2.09 l/sec/ha, the land area of ??Paddy I is 3,128 ha can be irrigated, Paddy II land area is 3,128 ha, and palawija (corn) land area is 3,122.96 ha with a planting intensity of 200%. The maximum profit of crop production that can be obtained for a year in alternative 21 is IDR 43,831,792,674.